2013
DOI: 10.1002/cbf.2942
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of melatonin in a rat model of caerulein‐induced acute pancreatitis

Abstract: The purpose of our study was to evaluate the protective effect of melatonin in a rat model of caerulein-induced acute pancreatitis. For the induction of experimental acute pancreatitis, four subcutaneous injections of caerulein (20 mgkg–1 body weight) were given to Wistar rats at 2-h intervals. Melatonin was injected intraperitoneally (25 mg kg–1 body weight) 30 min before each caerulein injection. After 12 h, rats were sacrificed by decapitation. Blood and pancreas samples were collected and processed for ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…In general, scientific evidence reinforces the future use of antioxidant supplementation in several pathological conditions. Taking in account previous works of our research group (Carrasco et al, 2013 , 2014a , b ) and other authors, both preventive and therapeutic uses of antioxidants have been reported to reduce not only oxidative stress related parameters but also inflammatory response and pain in several diseases. As mentioned earlier, it has been demonstrated that current drugs used in the management of different kinds of NP are ineffective and usually not safe for the patient.…”
Section: Introductionmentioning
confidence: 54%
“…In general, scientific evidence reinforces the future use of antioxidant supplementation in several pathological conditions. Taking in account previous works of our research group (Carrasco et al, 2013 , 2014a , b ) and other authors, both preventive and therapeutic uses of antioxidants have been reported to reduce not only oxidative stress related parameters but also inflammatory response and pain in several diseases. As mentioned earlier, it has been demonstrated that current drugs used in the management of different kinds of NP are ineffective and usually not safe for the patient.…”
Section: Introductionmentioning
confidence: 54%
“…Previous experimental studies have shown that pretreatment with melatonin could prevent pancreatic inflammation and radically reduce pancreatic tissue damage in rats subjected to acute pancreatitis in different experimental models [13,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73]. This was evidenced by histological assessment of pancreatic tissue and prominent decline of the inflammatory markers, such as edema, neutrophil infiltration, and vacuolization of the acinar cells [60,61,62,63,73].…”
Section: Melatonin System and Acute Pancreatitismentioning
confidence: 99%
“…This was evidenced by histological assessment of pancreatic tissue and prominent decline of the inflammatory markers, such as edema, neutrophil infiltration, and vacuolization of the acinar cells [60,61,62,63,73]. In animals with acute pancreatitis pretreated with melatonin, there was a significant reduction in the plasma morphometric indicators of pancreatic inflammation severity, blood levels of the enzymes, amylase and lipase, and blood levels of pro-inflammatory cytokines (e.g., TNFα, IL-1β, and IL-6), whereas anti-inflammatory interleukins IL-10 and IL-4 were increased [10,59,62,63,64,65,66,67,68,69,70]. The antioxidant effect of melatonin was expressed as a reduction of lipid peroxidation products (MDA + 4-HNE) in the pancreas and was accompanied by increased activity of antioxidant enzymes SOD, CAT, GPx, and GSH [62,63,64,65,66,67,69,70].…”
Section: Melatonin System and Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…The rescue study by MT injection into the WT goats with LPS stimulation confirmed that the protective effects of transgenic goats on LPS were attributed to the high levels of endogenously produced MT. This is the first study to show that a high level of endogenous MT per se suppresses the toxic effects of LPS in large animals [59,60]. …”
Section: Discussionmentioning
confidence: 99%